2018
DOI: 10.21276/ijcmr.2018.5.4.6
|View full text |Cite
|
Sign up to set email alerts
|

HbA1C and its Correlation with Lipid Profile in Acute Myocardial Infarction

Abstract: Introduction:Diabetes mellitus is present in as many as 30% of patients hospitalized with acute coronary syndromes. It has been recognized for some time that diabetics experience a greater mortality during the acute phase of myocardial infarction and a higher morbidity in the postinfarction period. The main contributory factors for these complications are uncontrolled diabetes mellitus and dyslipedemia. HBA1C level is gold standard in knowing control of diabetes mellitus and its complications. The lipid abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…A closer examination revealed that LDL-C levels had a negative correlation only with triglycerides and had positive correlations with SBP, HbA1C, HDL-C levels, and triglycerides in females. This was supported by a study conducted by Bhattacharjee et al [ 30 ] that reported that LDL-C levels was significantly correlated with HbA1C in a positive direction among myocardial infarction patients. A study among diabetes patients in Iran found that LDL-C levels was significantly positively correlated with both DBP and SBP [ 31 ].…”
Section: Discussionsupporting
confidence: 67%
“…A closer examination revealed that LDL-C levels had a negative correlation only with triglycerides and had positive correlations with SBP, HbA1C, HDL-C levels, and triglycerides in females. This was supported by a study conducted by Bhattacharjee et al [ 30 ] that reported that LDL-C levels was significantly correlated with HbA1C in a positive direction among myocardial infarction patients. A study among diabetes patients in Iran found that LDL-C levels was significantly positively correlated with both DBP and SBP [ 31 ].…”
Section: Discussionsupporting
confidence: 67%
“…Their correlation between HbA1c and HDL-C was negative and was statistically non-significant. A study in India reported similar findings of direct significant correlation between HbA1c and TC, TG, LDL-C, TC/HDL-C, LDL-C/HDL-C and there was inverse correlation between HbA1c and HDL [ 29 ], while another study reported that HbA1c levels had a significant direct relationship with TC, TG and LDL-C but not with HDL-C [ 35 ].…”
Section: Discussionmentioning
confidence: 86%
“…This prevalence was consistent with findings of Bhattacharjee et al . who found poor glycaemic control in 60% of their patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 A study from north eastern Indian population investigated the lipid profile and its correlation with HbA1c levels in incidence of myocardial infarction, which concluded that 60% patients with myocardial infarction had poor glycaemic control and found that the serum HbA1c level has direct relationship with the serum lipid profile and is indirectly associated with levels of HDL cholesterol. 27 A study conducted by Anand et al established that serum HbA1c levels, adequate glycaemic control, and lipid profile screening help to identify high-risk patients for timely diagnosis of hyperlipidaemia, hence decreases the incidence of cardiovascular diseases and peripheral vascular complications through appropriate interventions. 28 Mahajan et al conducted a study, which showed positive correlation of HbA1c with LDL, triglycerides, total cholesterol, high-density lipoprotein, very-low-density lipoprotein, and low-density lipoprotein C levels.…”
Section: Discussionmentioning
confidence: 99%